Epoxyeicosatrienoic acids inhibit the activation of NLRP3 inflammasome in murine macrophages. Issue 12 (26th May 2020) - Luo, Xiao‐Qin; Duan, Jia‐Xi; Yang, Hui‐Hui; Zhang, Chen‐Yu; Sun, Chen‐Chen; Guan, Xin‐Xin; Xiong, Jian‐Bing; Zu, Cheng; Tao, Jia‐Hao; Zhou, Yong; Guan, Cha‐Xiang
Abstract: Epoxyeicosatrienoic acids (EETs) derived from arachidonic acid exert anti‐inflammation effects. We have reported that blocking the degradation of EETs with a soluble epoxide hydrolase (sEH) inhibitor protects mice from lipopolysaccharide (LPS)‐induced acute lung injury (ALI). The underlying mechanisms remain essential questions. In this study, we investigated the effects of EETs on the activation of nucleotide‐binding domain leucine‐rich repeat‐containing receptor, pyrin domain‐containing‐3 (NLRP3) inflammasome in murine macrophages. In an LPS‐induced ALI murine model, we found that sEH inhibitor 1‐trifluoromethoxyphenyl‐3‐(1‐propionylpiperidin‐4‐yl), TPPU, profoundly attenuated the pathological injury and inhibited the activation of the NLRP3 inflammasome, characterized by the reduction of the protein expression of NLRP3, ASC, pro‐caspase‐1, interleukin precursor (pro‐IL‐1β), and IL‐1β p17 in the lungs of LPS‐treated mice. In vitro, primary peritoneal macrophages from C57BL/6 were primed with LPS and activated with exogenous adenosine triphosphate (ATP). TPPU treatment remarkably reduced the expression of NLRP3 inflammasome‐related molecules and blocked the activation of NLRP3 inflammasome. Importantly, four EETs (5, 6‐EET, 8, 9‐EET, 11, 12‐EET, and 14, 15‐EET) inhibited the activation of NLRP3 inflammasome induced by LPS + ATP or LPS + nigericin in macrophages in various degree. While the inhibitory effect of 5, 6‐EET was the weakest. Mechanismly, EETs profoundly decreased the content of reactive oxygen species (ROS) and restored the calcium overload in macrophages receiving LPS + ATP stimulation. In conclusion, this study suggests that EETs inhibit the activation of the NLRP3 inflammasome by suppressing calcium overload and ROS production in macrophages, contributing to the therapeutic potency to ALI. Abstract : We have reported that blocking the degradation of epoxyeicosatrienoic acids (EETs) derived from arachidonic acid could attenuate the lipopolysaccharide‐induced acute lung injury (ALI) in mice. The underlying mechanisms remain important questions. Herein, we found that EETs inhibit the activation of nucleotide‐binding domain leucine‐rich repeat‐containing receptor, pyrin domain‐containing‐3 inflammasome by suppressing calcium overload and reactive oxygen species production in macrophages, contributing to the therapeutic potency to ALI.